Are Insomnia Type Sleep Problems Associated With a Less Physically Active Lifestyle? A Cross-Sectional Study Among 7,700 Adults From the General Working Population - Bláfoss, Rúni; Sundstrup, Emil; Jakobsen, Markus Due; Bay, Hans; Garde, Anne Helene; Andersen, Lars Louis (Frontiers in Public Health, 2019)
Background: Sleep problems are common in the general population and negatively affect both private and work life. A vicious circle may exist between poor sleep and an unhealthy lifestyle. For example, poor sleep may drain the energy to do health-promoting physical activity during leisure-time after work. The aim of the present study was to investigate the association between sleep problems and the duration of low- and high-intensity leisure-time physical activity in sedentary and physical workers. Methods: This cross-sectional study employ data from the Danish Work Environment Cohort Study in 2010, where currently employed wage-earners in Denmark on daytime schedule (N=7706) replied to questions about sleep quality (Bergen Insomnia Scale) and participation in low- and high-intensity leisure-time physical activity. Associations were modeled using general linear models controlling for various confounders. Results: Workers with high levels of sleep problems reported less high-intensity leisure-time physical activity. Specifically, the weekly duration of high-intensity leisure-time physical activity was 139 (95%CI 111-168), 129 (95%CI 101-158) and 122 (95%CI 92-151) mins in sedentary workers with sleep problems <1, 1-3 and ≥3 days per week, respectively. The same pattern was observed among physical workers. In sedentary workers ≥50 years, the fully adjusted model showed a weekly duration in high-intensity physical activity during leisure of 122 (95%CI 83-161), 102 (95%CI 64-141) and 90 (95%CI 51-130) among those with sleep problems <1, 1-3 and ≥3 days per week, respectively. Conclusions: Workers, particularly sedentary older workers, having sleep problems report less high-intensity leisure-time physical activity. These data suggest that a vicious circle may indeed exist between poor sleep and reduced leisure-time physical activity.